Development of Arabic Comics in Qiraah Learning for 12th Grade Students at the Indonesian School in Riyadh - Rodhotul Jannah; Moh. Nurul Huda; Kiki Sakinatul Fuad (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This study aims to develop Arabic comic media as an innovative solution in qirā’ah (reading) learning for Year 12 students at the Indonesian Embassy School in Riyadh. The background of this research is based on findings of a gap in the learning process, where students experience difficulties in integrating their understanding of text meaning with the analysis of linguistic rules (nahwu and shorof) due to the separation of the focus of the material taught by different teachers. This study uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects are Grade XII students at the Indonesian Embassy School in Riyadh. The validation results show that the Arabic comic media obtained an average score of 96% from media experts (Very Suitable) and 80% from subject matter experts (Suitable). In addition, limited trials showed very positive student responses with an average score of 88% (Very Suitable), especially in terms of visual aspects and interest. Thus, this Arabic comic media is declared very suitable for use and has been proven to bridge the integration between language proficiency and linguistic analysis in a visual, interactive, and interesting way, especially in a multicultural context.